2020
DOI: 10.3390/su12239831
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Food Supply Chains: Is Shortening the Answer? A Literature Review for a Research and Innovation Agenda

Abstract: Short food supply chains (SFSCs) are increasingly garnering attention in food systems research, owing to their rising popularity among consumers, producers and policy-makers in the last few decades. Written with the aim to identify research gaps for the Horizon Europe research and innovation programme, this literature review provides a state of play of the definition and characterisation of SFSCs, and of their sustainability. Drawing on hypotheses about SFSC sustainability elaborated in an expert network in Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 121 publications
6
91
0
4
Order By: Relevance
“…However, a difference from developed countries like France, Austria, Hungary, Italy, etc. [3,8,69] is that the major channels of sales from the survey sample in Vietnam were through the local traders and markets. This implies that local traders will have a stronger power on setting products' prices and they will have more benefit, while small farmers will be more vulnerable because they will become accepted price actors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a difference from developed countries like France, Austria, Hungary, Italy, etc. [3,8,69] is that the major channels of sales from the survey sample in Vietnam were through the local traders and markets. This implies that local traders will have a stronger power on setting products' prices and they will have more benefit, while small farmers will be more vulnerable because they will become accepted price actors.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of studies showed that SFSCs created benefits for the whole societies or specific farmers [59,60], but most of the researches were carried out in developed countries like Scotland, England, Wales, Ireland, France, Greece, Finland, Poland, Germany, Italy, etc. [69].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the COVID-19 crisis, GLM has emerged as a hot topic, and agri-food supply chain resilience turned out to be of critical importance, especially since global chains have been mainly dependent on logistics, in order to resist this unforeseen shock [131]. From the point of view of practical implications, managers involved in GLM application and firm effectiveness assessment would be in a position to keep track of the status of GLM practices implemented, and to suggest which particular GLM aspects require more attention and resources to be allocated for satisfactory development, so as to enhance specific performance dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to anticipate and prepare for such disruptions seems fundamental to succeed in this endeavor [7]. Some of the suggested strategies for achieving this are to increase FSC resilience by shortening the supply chain [8] and the use of digital technologies [9].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to shortening the supply chain, Short Food Supply Chains (SFSCs) have been gaining attention in food systems research during the last decade. SFSCs comprise a wide variety of initiatives, such as community-supported agriculture (CSA), farmers' markets and farmer shops, often characterized by geographical and relational proximity, local food and commitment to co-operation [8]. Several benefits are expected from SFSCs, such as "economic benefits to both producers and consumers, strengthening social relations, preserving the environment, improving nutritional aspects, and enhancing local development" [10] (p. 3).…”
Section: Introductionmentioning
confidence: 99%